CARBON DIETING: LATENT ANCILLARY RIGHTS TO CARBON OFFSETS IN CONSERVATION EASEMENTS (Utah Environmental Law Review, 2009)
Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} This article addresses a single systematic methodology for mitigating global greenhouse gases in the atmosphere. That methodology is the creation, sale, and retirement of “carbon offsets.” Regarding carbon offsets, this article focuses on the use of conservation easements to underpin carbon offset projects. As this article explains, it is within the language of the much-used legal tool of conservation easements that we find what this article describes as “latent ancillary rights” from which we can create and allocate carbon offsets. In particular, this article examines what language, if any, should be inserted in conservation easements to insure the creation and desired allocation of carbon offsets. Because California has developed and implemented many of the first and most effective anti-global warming programs, including a climate registry and forest protocol based largely on carbon offsets, California is used as a model in this article.